How wide is a fault damage zone? Using network topology to examine how fault-damage zones overprint regional fracture networks. (May 2021) - Hansberry, Rowan L.; King, Rosalind C.; Holford, Simon P.; Hand, Martin; Debenham, Natalie
Abstract: Topological analysis of networks of linear features has recently gained popularity in structural geology, as it provides a robust system of fracture network characterisation with consistent terminology. This approach has mainly been applied by using discontinuous sample areas to characterise topology of a region, or geological feature (e.g. Procter and Sanderson, 2018). We apply network topology to investigate spatial variation of a natural fracture network in the damage zone of the Castle Cove Fault, Otway Basin, Victoria. The Castle Cove Fault's associated fracture network occurs in the hanging-wall Eumeralla Formation, a fine-to medium-grained volcanogenic sandstone or Early Cretaceous age. Topological characterisation of the Castle Cove Fault damage-zone identified an increase in the two-dimensional intensity of fracturing in the hanging-wall at a distance 70 m from the fault, reaching a maximum 40 m from the fault, indicating the extent of the fault-damage zone is between 40 and 70 m from the main fault. Maximum fracture intensity values decay with a power law relationship with respect to distance from the fault plane, averaging 0.06 adjacent to the fault, and 0.02 within what is interpreted as the regional fracture network, 70 m + outboard of the fault. Fracture orientations in the damage zone are synthetic and antithetic with respect to the 60° dip to the NW of the of the Castle Cove Fault, with these fault-related fractures overprinting an existing regional fracture network, creating high fracture network connectivity within the fault-damage zone. Our results show that network topology is a powerful tool for quantifying and visualising the properties of fracture networks associated with crustal-scale faults. Highlights: Network topology provides a quick, robust method for quantitative analysis of fracture networks. This allows assessment of the spatial variation of parameters relating to fracture intensity and connectivity. Topological parameters indicating the scaling of fault-damage zones is consistent with other estimates. Damage zone fractures overprint background fractures, creating an overlap of geometries and high connectivity.